Experimentelle Analyse der Stabilisierungseigenschaften von abgehobenen eingeschlossenen nicht-vorgemischten Drallflammen - Fokaides, Paris A. (KIT Scientific Publishing, 2010)
Subject of this work was the experimental investigation of an confined, lifted, non-premixed swirl flame by employing a novel airblast nozzle. For the time-resolved determination of all three velocity components, a measurement campaign was carried out using a commercial 3-D LDA system. Concentration and temperature measurements in the reacting field were also performed to better understand the complex turbulent and chemical interactions.